2019
DOI: 10.1111/neup.12619
|View full text |Cite
|
Sign up to set email alerts
|

FHL1‐mutated reducing body myopathy

Abstract: Here, we report about reducing body myopathy, associated with a mutation in the four and a half LIM domain 1 gene (FHL1), identified in a 40‐year‐old woman who was suffering from subtle muscle weakness since the age of six and a limping gait since the age of 22 years. In addition to her elevated muscle enzyme level and magnetic resonance imaging, myopathy was highly suspected considering progression of symptoms. Nerve conduction studies and electromyogram suggested myopathy. The muscle biopsy revealed severe d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In rare myopathies like FHL1 ‐related RBM, muscle imaging modalities hold promise as disease biomarkers to facilitate diagnosis and to help monitor disease progression and empower interventional clinical trials 10–12 . In a few case studies of FHL1 ‐related RBM patients, muscle MRI studies have suggested a distinct pattern of muscle involvement in the lower extremities: sparing of gluteus maximus muscle, and selective involvement of posteromedial thigh muscles, medial gastrocnemius, and soleus muscles 13–16 . Muscle ultrasound and cardiac MRI studies are not extensively reported in the literature in patients with FHL1 ‐related RBM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In rare myopathies like FHL1 ‐related RBM, muscle imaging modalities hold promise as disease biomarkers to facilitate diagnosis and to help monitor disease progression and empower interventional clinical trials 10–12 . In a few case studies of FHL1 ‐related RBM patients, muscle MRI studies have suggested a distinct pattern of muscle involvement in the lower extremities: sparing of gluteus maximus muscle, and selective involvement of posteromedial thigh muscles, medial gastrocnemius, and soleus muscles 13–16 . Muscle ultrasound and cardiac MRI studies are not extensively reported in the literature in patients with FHL1 ‐related RBM.…”
Section: Introductionmentioning
confidence: 99%
“… 10 , 11 , 12 In a few case studies of FHL1 ‐related RBM patients, muscle MRI studies have suggested a distinct pattern of muscle involvement in the lower extremities: sparing of gluteus maximus muscle, and selective involvement of posteromedial thigh muscles, medial gastrocnemius, and soleus muscles. 13 , 14 , 15 , 16 Muscle ultrasound and cardiac MRI studies are not extensively reported in the literature in patients with FHL1 ‐related RBM.…”
Section: Introductionmentioning
confidence: 99%